Reducing Anxiety in Patients Undergoing Hemodialysis with Spiritual Mindfulness Based On Breathing Exercise - Tata Mahyuvi; Novita Sari (Journal Of Nursing Practice, 2024)
ABSTRACT Background: Patients with chronic kidney failure say that they are anxious because they see the tubes flowing blood, costs that must be incurred each time undergoing therapy, anxiety because invasive procedures will be carried out, and uncertainty about recovery. Objective: The purpose of this study was to analyze the Spiritual Mindfulness Based On Breathing Exercise on the anxiety of patients on Hemodialysis. Methods: The research design uses a quasi-experiment with a pre and posts group design control. The population of all chronic kidney failure patients at A. Yani Surabaya Islamic Hospital is 70 people. The sample size is 32 respondents. The sampling technique is purposive sampling. The intervention group was given Spiritual Mindfulness Based On Breathing Exercises and the control group was given intervention according to hospital standards. Analysis used the Wilcoxon with a significant value of ?? < 0.05. Results: the anxiety level p-value of 0.000 in the intervention group and the control group p-value of 0.109 which means there is an effect of Spiritual Mindfulness Based On Breathing Exercises on patient anxiety on Hemodialysis. Conclusion: Spiritual Mindfulness Based On Breathing Exercise is effective in reducing anxiety in chronic kidney failure patients undergoing hemodialysis and the technique is easy to perform.